Menggali Motif Dibalik Pemahaman Perpajakan Para Pelaku Usaha Mikro, Kecil dan Menengah (UMKM) Yang Tedaftar Di Website Desa Kesiman Petilan - Ni Nyoman Santhi Dewi; Cokorda Gde Bayu Putra; I Wayan Budi Satriya (UNHI Press, 2026)
ABSTRACT The purpose of this “research is to explore the underlying motives that drive tax noncompliance among Micro, Small, and Medium Enterprises (MSMEs). The data were gathered through detailed interviews and direct field observations, and documentation involving 18 active MSME actors from the culinary, handicraft, and fashion sectors. The findings indicate that MSME tax noncompliance is driven by low tax awareness and understanding, weak business management systems, and administrative fear or assumptions of high tax burdens. Most MSME actors do not have a Taxpayer Identification Number (NPWP) and have not once filed their annual tax returns (SPT), while only a few are compliant due to prior mentoring experiences. Noncompliance motives are categorized into unintentional noncompliance due to the absence of tax outreach and mentoring from both the village government and tax authorities further exacerbates the situation.